Antalya Kaleiçi and Its Surroundings on the 1905 Maps - Evren Dayar (Art-Sanat)
Maps are highly valuable as historical sources because they offer a visual representation of the reality, they depict during the time they were created. The significance of maps as historical resources becomes even more apparent when studying cities like Antalya, which have experienced significant damage to their historical structures, or when attempting to identify structures that no longer exist today. The maps become crucial tools for reconstructing the historical fabric of such cities and bridging the gap between the past and the present. This article aims to evaluate two maps of Antalya prepared on March 27, 1905, utilizing archival documents, inscriptions, and various visual sources. These maps, created to document the damage to the walls and towers of Antalya in the early 20th century, are highly functional for identifying key reference points in the city and understanding urban modernization. In the article, based on the 1905 maps, the city’s harbor, Antalya Citadel (Tophane), Kaleiçi neighborhoods, city walls, city gates, and the settlement areas outside the walls are depicted, presenting a panoramic view of early 20th-century Antalya. In addition, the 1905 maps provide significant information about some structures that are no longer present today. Through the 1905 maps, it has been possible to identify the bathhouse structure in the citadel, the Bayrakdar Baba Tomb, and the original location of the clock tower, claimed to have been constructed in 1921.